ACQUISITION OF WRITING IN THE EARLY STAGES OF LEARNING ENGLISH - S. U. Jumanazarov (American Journals, 2022)
The performance of written assignments in English is associated with very specific requirements set out in educational and methodological complexes and training programs for students studying foreign languages. This article discusses the problems faced by a teacher when preparing students, both for writing various types of letters and written statements on given topics. Based on his own experience of working with students, the author offers his practical recommendations for improving the writing skills of students studying English.
Keywords: teaching writing, educational and methodological complexes, writing problems, improving the writing skills